An mHealth intervention to improve nurses' atrial fibrillation and anticoagulation knowledge and practice: the EVICOAG study. (1st January 2019) - Ferguson, Caleb; Hickman, Louise D; Phillips, Jane; Newton, Phillip J; Inglis, Sally C; Lam, Lawrence; Bajorek, Beata V
Abstract: Background: There is a need to improve cardiovascular nurses' knowledge and practices related to stroke prevention, atrial fibrillation and anticoagulation therapy. Aims: The aim of this study was to evaluate the efficacy of EVICOAG – a novel mHealth, smartphone-based, spaced-learning intervention on nurses' knowledge of atrial fibrillation and anticoagulation. Methods: Nurses employed in four clinical specialties (neuroscience, stroke, rehabilitation, cardiology) across three hospitals were invited to participate. In this quasi-experimental study, 12 case-based atrial fibrillation and anticoagulation learning scenarios (hosted by an mHealth platform) were delivered to participants' smartphones over a 6-week period (July–December 2016) using a spaced timing algorithm. Electronic surveys to assess awareness and knowledge were administered pre (T1) and post (T2) intervention. Results: From 74 participants recruited to T1, 40 completed T2. There was a 54% mean improvement in knowledge levels post-intervention. The largest improvement was achieved in domains related to medication interaction and stroke and bleeding risk assessment. Post-intervention, those who completed T2 were significantly more likely to use CHA2 DS2 -VASc (2.5% vs. 37.5%) and HAS-BLED (2.5% vs. 35%) tools to assess stroke and bleeding risk, respectively ( P <0.01). Conclusion: The EVICOAG intervention improved nurses' knowledge of atrial fibrillation and anticoagulation, and influenced their uptake and use of stroke and bleeding risk assessment tools in clinical practice. Future research should focus on whether a similar intervention might improve patient-centred outcomes such as patients' knowledge of their condition and therapies, medication adherence, time in the therapeutic range and quality of life.